2023
DOI: 10.1039/d2ta08726j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrophobic side chains in poly(fluorenyl-co-aryl piperidinium) ionomers for durable anion exchange membrane fuel cells

Abstract: Durable and conductive catalyst layers are critical for anion exchange membrane fuel cells (AEMFCs) to achieve high power density and sufficient lifespan. Great efforts have been devoted to improving the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…One of the main conclusions was that AEMs with side chains attached to the backbone separated from the cationic groups were superior ion conductors in comparison with AEMs with side chains directly linked to the piperidinium cations. Lee and co-workers have directly compared the effects of having hexyl and octyl side chains, respectively, attached to either piperidinium cations or to fluorene units (Figure a) in the backbone . The study showed that side chains tethered to the cations reduced the alkaline stability and the conductivity, whereas the side chains placed on the fluorene units brought improved dimensional stability, ionic conductivity (up to 134 mS cm –1 ), mechanical properties and electrochemical stability.…”
Section: Aem For Use In Alkaline Solutions < 2 Mmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main conclusions was that AEMs with side chains attached to the backbone separated from the cationic groups were superior ion conductors in comparison with AEMs with side chains directly linked to the piperidinium cations. Lee and co-workers have directly compared the effects of having hexyl and octyl side chains, respectively, attached to either piperidinium cations or to fluorene units (Figure a) in the backbone . The study showed that side chains tethered to the cations reduced the alkaline stability and the conductivity, whereas the side chains placed on the fluorene units brought improved dimensional stability, ionic conductivity (up to 134 mS cm –1 ), mechanical properties and electrochemical stability.…”
Section: Aem For Use In Alkaline Solutions < 2 Mmentioning
confidence: 99%
“…Lee and co-workers have directly compared the effects of having hexyl and octyl side chains, respectively, attached to either piperidinium cations or to fluorene units (Figure 21a) in the backbone. 238 The study showed that side chains tethered to the cations reduced the alkaline stability and the conductivity, whereas the side chains placed on the fluorene units brought improved dimensional stability, ionic conductivity (up to 134 mS cm −1 ), mechanical properties and electrochemical stability. Li et al synthesized and investigated AEMs based on poly(arylene indole piperidinium) with different alkyl chains attached to the indole units (Figure 21b).…”
Section: Introduction Of Side Chainsmentioning
confidence: 99%
“…Anode flooding increased the mass transfer resistance of hydrogen, causing voltage loss, while cathode dry-out increased the nucleophilicity of hydroxide ions to attack the functional groups, resulting in degradation of ionomers and an increase in ohmic resistance. Kim, Mustain, and co-workers revealed that the water environment in fuel cells can be optimized by controlling the relative humidity (RH), gas flow rate, and polarity of ionomers in the cathode and anode. , …”
Section: Introductionmentioning
confidence: 99%
“…Dekel and co-workers pointed out that the improved hydroxide conductivity of AEM enhanced water diffusion through the membrane, which is critical for long-term operation of AEMFCs . In addition, inappropriate operation conditions also cause the limited fuel cell performance and durability of AMEFCs. As has been well elucidated, the water environment of AEMFCs is much more complicated than that of PEMFCs, ,, and the severe water imbalance caused by the water generation reaction in the anode and the water consumption reaction in the cathode can accelerate the degradation of fuel cells . Moreover, the transport of OH – ions from the cathode to the anode accompanied by 8 water molecules further exacerbated the imbalance of water distributions .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high ionic conductivity and evident microphase separation, the prepared AEMs can reach a maximum power density of 785.6 mW cm −2 . Hu et al 31 reported a set of AEMs with varying lengths of hydrophobic side chains located at different graft positions. Because of the apparent microphase separation, the obtained AEMs had an ionic conductivity of 143.2 mS cm −1 and a peak power density (PPD) of 2.6 W cm −2 .…”
Section: Introductionmentioning
confidence: 99%